Postcard from Marianne Homburger to Max Bredig, November 12, 1938 - Homburger, Marianne (1938)
Postcard from Marianne Bredig (1903-1986) to her brother, Max Albert Bredig (1902-1977). Marianne tells Max that their father and her family are doing well.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944